Enfrentamento ao preconceito racial na terceira idade por meio de círculos de cultura - Madeira, Bárbara Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Amidst the social problems of Brazil, including racial prejudice and geronticide, this study aims to discuss such issues as the insertion of the elderly in the contemporary and technological educational process, as well as racial prejudice in seniors in the northwest São Paulo. To achieve these objectives Freirean circles of culture for the years of 2019/2020 were reproduced. Regarding the qualitative methodology, the essay produced by the participants of Open University for Seniors (UNATI/UNESP) in blog Virtual Center for Studies and Cultures of the Rural World (VILLELA, 2014) were analyzed. Through these writings we can observe a process of awareness of the “Unatianos” through the passage from naive transitivity to critical transitivity. As for the analysis of the quantitative data with respect to racial prejudice in caipira territory, a survey was carried out on the social medias such as Facebook, via Facebook Group Eletro Folk Orquestra. The main results of the survey show, that there exists subtle racial prejudice in the northwest of São Paulo.

Em meio aos problemas sociais presentes no Brasil como o preconceito racial e o gerontocidio, este trabalho pretende numa perspectiva sócio-histórica problematizar questões como a inserção do idoso no processo educativo contemporâneo e tecnológico, bem como o preconceito racial existente na terceira idade no Noroeste Paulista. Para atender a estes objetivos foram feitas reproduções dos Círculos de Cultura freirianos nos anos de 2019/2020. Como metodologia qualitativa foram analisados textos produzidos pelos participantes da Universidade Aberta à Terceira Idade (UNATI/UNESP) no blog de aula Centro Virtual de Estudos e Culturas do Mundo Rural (VILLELA, 2014). Por meio destas escritas podemos observar um processo de conscientização dos Unatianos por meio da passagem da transitividade ingênua para a transitividade crítica. Para a análise de dados quantitativos a respeito do preconceito racial no território caipira foi realizado um survey encaminhado por meio de mídias sociais como o Grupo Eletro Folk Orquestra do Facebook. Como resultados principais, o survey mostrou a existência do preconceito racial de forma sutil no noroeste paulista.
Confronting racial prejudice in the third age through circles of culture
Keywords: Afro-brazilian culture; Third age; Circle of culture; Cultura Afro-brasileira; Terceira idade; Círculos de cultura